Intensive Exercise Reduces the Fear of Additional Falls in Elderly People: Findings from the Korea Falls Prevention Study - Oh, Dong Hyun (The Korean Association of Internal Medicine, 2012)
BACKGROUND/AIMS: Falls among older people are a major public health problem and may result in fracture, medical complications that require hospitalization, and fear of additional falls. Given the prevalence and impact of the fear of falling again, reducing the incidence of falls is important to prevent additional falls. This study analyzed whether exercise programs decrease the fear of future falls in elderly patients who have fallen previously. METHODS: A randomized controlled study was performed that included 65 elderly community-dwelling subjects who had fallen in the previous year. Subjects were randomized into two groups: an exercise group (EG, n = 36) and a control group (CG, n = 29). The EG participated in three exercise sessions per week for 12 weeks. Muscle strength, balance, agility, flexibility, and muscular endurance were measured at baseline and after 12 weeks. RESULTS: After the 12-week exercise program, the subjects in the EG demonstrated remarkable improvement in their walking speed, balance (p = 0.003), back strength (p = 0.08), lower extremity strength (p = 0.004), and flexibility (p < 0.001). When asked whether they were afraid of falling, more participants in the EG than in the CG responded "not at all" or "a little." CONCLUSIONS: The 12-week exercise program described here reduced the fear of falling (p = 0.02). It also improved the balance, flexibility, and muscle strength of the participants and was associated with improved quality of life.